Acid-resistant, alkali-resistant, and corrosion-resistant silicone tube and preparation method thereof
By using modified graphite phase carbon nitride and fluoro-containing silane compounds in silicone tubes to form a carbon nitride barrier layer, the corrosion problem of silicone tubes in acid/alkaline liquids is solved, which significantly reduces cyclosiloxane migration and improves the It has acid and alkali corrosion resistance, ensuring the safety of the drug liquid and the stability of the material.
Patent Information
- Application Number
- CN202411280277.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing silicone tubes have a high content of cyclosiloxanes produced and migrated due to corrosion during the transportation of acid/alkaline liquids, which affects the quality of drugs and human health, and their acid and alkali corrosion resistance is insufficient.
Using modified graphite phase carbon nitride and fluoro-containing silane compounds as fillers, the silicone tubes are improved by preparing modified graphite phase carbon nitride and forming a carbon nitride barrier layer in the silicone tube to block and shield acidic/alkaline ions. Acid and alkali corrosion resistance.
The cyclosiloxane content of silicone tubes migrate in acid/alkali medicine liquid is significantly reduced, the acid-base corrosion resistance of silicone tubes is improved, the liquid pollution is prevented, and the material stability is enhanced.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicone tube production, and specifically relates to an acid-, alkali-, and corrosion-resistant silicone tube and a preparation method thereof. Background Art
[0002] Silicone tubes are often used in the production of drugs for transportation, filtration, filling and other processes. They are key components in the production of drugs, and their quality will directly affect the safety and quality of the final drug products. Silicone tubes are mainly made of different types of silicone rubber, with excellent thermal stability, heat dissipation and weather resistance, and high oxidation resistance. The processing technology is complex. After the low molecular weight cyclosiloxane is ring-opened and polymerized to form high molecular weight polysiloxane, it is then vulcanized with various reinforcing fillers such as white carbon black under heating and pressurization conditions.
[0003] Silicone tubes made of silicone rubber have excellent surface properties and physiological inertness, but their acid and alkali corrosion resistance is poor. Acid / alkali ionic substances can break the silicon-oxygen bonds in silicone rubber to form cyclosiloxanes. During drug delivery, cyclosiloxanes may migrate into the drug solution, affecting the quality of the drug and human health. Among them, small molecule cyclosiloxanes such as hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5) and dodecamethylcyclohexasiloxane (D6) in cyclosiloxanes may be carcinogenic and bioaccumulative. In addition, the National Drug Administration Drug Evaluation Center issued the "Technical Guidelines for Compatibility Studies of Plastic Component Systems Used in the Production of Chemical Injections (Trial)" on October 21, 2020, which clearly stated that "for silicone tubes...particular attention should be paid to silicone rubber oligomer components (such as D3D4D5D6 cyclosiloxanes)..."
[0004] Therefore, in order to reduce the content of cyclosiloxanes produced and migrated due to corrosion in silicone rubber during the transportation of acid / alkaline liquids, developing silicone rubber with excellent acid and alkali corrosion resistance is one of the key research directions. Summary of the invention
[0005] The purpose of the present invention is to provide an acid-resistant, alkali-resistant and corrosion-resistant silicone tube and a preparation method thereof, so as to reduce the content of cyclosiloxane produced and migrated due to corrosion in the prepared silicone rubber during the transportation of acid / alkaline liquid medicine, and prevent the prepared silicone rubber from contaminating the liquid medicine.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] An acid-resistant, alkali-resistant and corrosion-resistant silicone tube comprises the following raw materials in parts by weight:
[0008] 100 parts of methyl vinyl silicone rubber;
[0009] 22-25 parts of modified graphite phase carbon nitride;
[0010] 13-15 parts of white carbon black;
[0011] 12-15 parts of polymethyl hydrogen siloxane;
[0012] 2-3 parts of vulcanizing agent;
[0013] 1 to 3 parts of platinum catalyst.
[0014] Furthermore, the modified graphite phase carbon nitride is prepared by the following steps:
[0015] S1. Place a nitrogen-containing compound in a crucible, then place it in a muffle furnace, heat it to 550-580°C at a heating rate of 9-11°C / min, and continue calcining at a constant temperature for 3-4 hours. After calcination, cool it naturally to room temperature to obtain a solid product, grind the solid product through a 400-mesh sieve to obtain bulk carbon nitride;
[0016] S2. Stir and add bulk carbon nitride to 95% sulfuric acid, stir magnetically for 1 to 2 hours, filter, collect solid components, wash the solid components with deionized water until neutral, place the washed solid components in 50% ethanol-pure water solution by volume, stir ultrasonically for 30 to 50 minutes, add fluorine-containing silane compound by stirring, continue ultrasonic stirring for 4 to 5 hours, and after the ultrasonic stirring is completed, centrifuge and dry to obtain modified graphite phase carbon nitride.
[0017] Furthermore, the nitrogen-containing compound is one of urea, melamine and guanidine hydrochloride.
[0018] Furthermore, the usage ratio of 95% sulfuric acid, bulk carbon nitride, 50% ethanol-pure water solution, and fluorine-containing silane compound in S2 is 200mL:20g:200mL:25-30g.
[0019] Furthermore, the fluorine-containing silane compound is prepared by the following steps:
[0020] N,N-dimethylformamide is added to the reactor with stirring, and nitrogen is filled in for protection. Then, tridecafluorooctanol and (3-epoxypropoxy)propyltrimethoxysilane are added thereto with stirring, and the mixture is stirred for 3 to 5 minutes. The mixture is heated to 40 to 50° C., and stirred at a constant temperature for 5 to 10 minutes. Then, triethylamine is added thereto with stirring. After the addition of triethylamine is completed, the mixture is heated to 140 to 155° C., and stirred at a constant temperature for 5 to 6 hours. After the stirring is completed, the mixture is cooled to room temperature to obtain a mixture. During the above reaction process, the alcoholic hydroxyl group in tridecafluorooctanol can open the end epoxy group of (3-epoxypropoxy)propyltrimethoxysilane and form a new hydroxyl group by bonding under the catalytic action of triethylamine. The reaction process is shown below, and the prepared mixture is finally obtained. After the mixture is subjected to reduced pressure distillation, Amberlyst-15 ion exchange resin is added thereto with stirring, and the mixture is stirred at room temperature for 20 to 30 minutes to adsorb the remaining catalyst triethylamine. After the stirring is completed, the mixture is filtered, and the filtrate is collected to obtain a fluorine-containing silane compound.
[0021] .
[0022] Furthermore, the usage ratio of N,N-dimethylformamide, tridecafluorooctanol, (3-epoxypropoxy)propyltrimethoxysilane, triethylamine, and Amberlyst-15 ion exchange resin is 500mL: 0.1-0.11mol: 0.1-0.105mol: 8.5-10.5g: 4.5-5.0g.
[0023] Furthermore, the vulcanizing agent is one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 2,4-dichlorobenzoylperoxide.
[0024] Furthermore, the method for preparing the acid-resistant, alkali-resistant and corrosion-resistant silicone tube comprises the following steps:
[0025] Mixing: Weigh the raw materials according to their weight and mix them in an internal mixer for mixing. The speed of the internal mixer is 30-50 r / min and the mixing time is 20-30 min. After mixing, a silica gel material is obtained;
[0026] Extrusion: placing the silicone material in a silicone extruder for extrusion molding, the extrusion temperature of the silicone extruder is 145-160°C, the extrusion rate is 5-15m / min, and after extrusion, a silicone tube is obtained;
[0027] Vulcanization: Place the silicone tube in a vulcanization furnace for vulcanization treatment. After the vulcanization treatment is completed, cool it to room temperature, and then inspect and package it to obtain an acid-resistant, alkali-resistant, and corrosion-resistant silicone tube.
[0028] Furthermore, the vulcanization treatment includes primary vulcanization and secondary vulcanization.
[0029] Furthermore, the temperature of the primary vulcanization is 165-175° C., the time of the primary vulcanization is 20-30 minutes, and after the primary vulcanization is completed, secondary vulcanization is performed, the temperature of the secondary vulcanization is 210-220° C., and the time of the secondary vulcanization is 1.5-2 hours.
[0030] Beneficial effects of the present invention:
[0031] The present invention provides an acid- and alkali-resistant and corrosion-resistant silicone tube and a preparation method thereof. The present invention introduces homemade modified graphite phase carbon nitride, and after testing, the acid / alkali corrosion resistance of the prepared silicone tube is significantly improved. The specific principles and effects are as follows:
[0032] When the silicone tube is transporting acidic / alkaline liquid medicine, the acidic / alkaline ions in the liquid medicine will break the silicon-hydrogen bonds in the molecules on the inner wall of the silicone tube, forming small molecular siloxanes that migrate into the liquid medicine. At the same time, the micropores generated after the break, the acidic / alkaline ions will further enter the interior of the silicone tube through the micropores, forming a vicious cycle of corrosion-breakage-migration-deep corrosion. Therefore, the present invention adds modified graphite phase carbon nitride to the silicone tube. Carbon nitride itself has excellent acid and alkali corrosion resistance. Carbon nitride is also commonly used as a corrosion-resistant filler in the prior art. However, corrosion resistance is an intrinsic property of carbon nitride. Adding it as a filler to the silicone tube cannot effectively affect the structure of siloxane in the silicone tube. Therefore, the present invention prepares modified graphite phase carbon nitride (g-C3N4). The present invention first prepares bulk carbon nitride, then exfoliates the bulk carbon nitride to obtain graphite phase carbon nitride, and then grafts the graphite phase carbon nitride. First, the graphite phase carbon nitride after exfoliation is dispersed. The thin sheet structure of the modified graphite phase carbon nitride has a blocking and shielding effect on acidic / alkaline ions. When the dosage is low and a covering shield cannot be formed, the addition of the thin sheet structure can also make the penetration path of the acidic / alkaline ions in the liquid medicine become tortuous. Then, the present invention uses a homemade fluorine-containing silane compound to graft-modify the graphite phase carbon nitride. The fluorine-containing silane compound contains a long fluorocarbon chain. The long fluorocarbon chain has excellent performance in migrating to the surface of the material, that is, surface self-migration. The present invention introduces a long fluorocarbon chain into the surface of the graphite phase carbon nitride, which helps to improve the surface migration of the graphite phase carbon nitride. At the same time, in the subsequent silicone tube vulcanization process, the migration of the modified graphite phase carbon nitride to the surface of the silicone tube material can be further improved under high temperature heating conditions. Finally, a carbon nitride barrier layer is formed on the inner and outer walls of the prepared silicone tube, which further inhibits the penetration of acidic / alkaline ions into the silicone tube material, and comprehensively improves the acid / alkali corrosion resistance of the prepared silicone tube. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] Preparation of fluorinated silane compounds:
[0036] 500 mL of solvent N,N-dimethylformamide (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to the reactor with stirring, and nitrogen was filled in for protection. Then 0.1 mol of tridecafluorooctanol (98.0%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 0.1 mol of (3-epoxypropoxy)propyltrimethoxysilane (98%; purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to the reactor with stirring, and the mixture was mixed for 3 min. The reactor was heated to 40 ° C and stirred at constant temperature for 5 min. Then 8.5 g of catalyst triethylamine (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to the reactor with stirring. After the catalyst was added, the reactor was heated to 140 ° C and stirred at constant temperature for 5 h. After completion, the mixture was cooled to room temperature to obtain a mixture. During the above reaction, the alcoholic hydroxyl group in tridecafluorooctanol can open the end epoxy group of (3-epoxypropoxy)propyltrimethoxysilane and form a new hydroxyl group by bonding under the catalytic action of triethylamine. The reaction process is shown below, and the prepared mixture is finally obtained. The mixture is then subjected to reduced pressure distillation to remove the solvent N,N-dimethylformamide and the catalyst triethylamine in the mixture, and then 4.5 g of Amberlyst-15 ion exchange resin (purchased from Shanghai Yuanye Biotechnology Co., Ltd.) is added to the mixture with stirring, and stirred at room temperature for 20 minutes to adsorb the remaining catalyst triethylamine. After stirring, the mixture is filtered and the filtrate is collected to obtain a fluorine-containing silane compound.
[0037] Example 2
[0038] Preparation of fluorinated silane compounds:
[0039] 500 mL of solvent N,N-dimethylformamide (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to the reactor with stirring, and nitrogen was filled in for protection. Then 0.11 mol of tridecafluorooctanol (98.0%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 0.105 mol of (3-epoxypropoxy)propyltrimethoxysilane (98%; purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to the reactor with stirring. The mixture was mixed for 5 min, and the reactor was heated to 50 ° C. and stirred at constant temperature for 10 min. Then 10.5 g of catalyst triethylamine (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to the reactor with stirring. After the catalyst was added, the reactor was heated to 150 ° C. and stirred at constant temperature for 6 h. After stirring, the mixture was cooled to room temperature to obtain a mixture. During the above reaction, the alcoholic hydroxyl group in tridecafluorooctanol can open the end epoxy group of (3-epoxypropoxy)propyltrimethoxysilane and form a new hydroxyl group through a bond under the catalytic action of triethylamine. The reaction process is shown below. Finally, the prepared mixture was obtained. The mixture was subjected to reduced pressure distillation to remove the solvent N,N-dimethylformamide and the catalyst triethylamine in the mixture. 5.0 g of Amberlyst-15 ion exchange resin (purchased from Shanghai Yuanye Biotechnology Co., Ltd.) was added to the mixture with stirring. The mixture was stirred for 30 minutes at room temperature to adsorb the remaining catalyst triethylamine. After stirring, the mixture was filtered and the filtrate was collected to obtain a fluorine-containing silane compound.
[0040] Example 3
[0041] Preparation of fluorinated silane compounds:
[0042] 500 mL of solvent N,N-dimethylformamide (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to the reactor with stirring, and nitrogen was filled in for protection. Then 0.1 mol of tridecafluorooctanol (98.0%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 0.105 mol of (3-epoxypropoxy)propyltrimethoxysilane (98%; purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to the reactor with stirring. The mixture was mixed for 5 min. The reactor was heated to 50 ° C. and stirred at constant temperature for 10 min. Then 10.5 g of catalyst triethylamine (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to the reactor with stirring. After the catalyst was added, the reactor was heated to 155 ° C. and stirred at constant temperature for 6 h. After stirring, the mixture was cooled to room temperature to obtain a mixture. During the above reaction, the alcoholic hydroxyl group in tridecafluorooctanol can open the end epoxy group of (3-epoxypropoxy)propyltrimethoxysilane and form a new hydroxyl group under the catalytic action of triethylamine. The reaction process is shown below, and the prepared mixture is finally obtained. The mixture is then subjected to reduced pressure distillation to remove the solvent N,N-dimethylformamide and the catalyst triethylamine in the mixture, and then 5.0 g of Amberlyst-15 ion exchange resin (purchased from Shanghai Yuanye Biotechnology Co., Ltd.) is added to the mixture with stirring, and stirred at room temperature for 30 minutes to adsorb the remaining catalyst triethylamine. After stirring, the mixture is filtered and the filtrate is collected to obtain a fluorine-containing silane compound.
[0043] Example 4
[0044] Preparation of modified graphite phase carbon nitride:
[0045] S1. 100 g of urea (AR; purchased from Tianjin Guangfu Technology Development Co., Ltd.) was placed in a covered ceramic crucible, and then placed in a muffle furnace (KSL-1200X; produced by Hefei Kejing Material Technology Co., Ltd.), and the temperature was increased to 550° C. at a heating rate of 9° C. / min, and the calcination was continued at a constant temperature for 3 h. After the calcination was completed, the mixture was naturally cooled to room temperature to obtain a solid product, and the solid product was ground through a 400-mesh sieve to obtain bulk carbon nitride;
[0046] S2. Add 20 g of bulk carbon nitride to 200 mL of 95% sulfuric acid (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) with stirring, stir magnetically for 1 hour, filter, and collect solid components, wherein the bulk carbon nitride is treated with acid to reduce the interlayer bonding force and achieve peeling, and the obtained solid component is mainly graphite phase carbon nitride. Wash the solid component with deionized water until it is neutral, and then place the washed solid component in 200 mL of 50% ethanol-pure water solution (prepared with anhydrous ethanol; anhydrous ethanol is purchased from Sinopharm Chemical Reagent Co., Ltd.) with a volume fraction of 50%, ultrasonically stir for 30 minutes, and then add 25 g of the fluorine-containing silane compound prepared in Example 1 above, continue ultrasonic stirring for 4 hours, and after the ultrasonic stirring is completed, centrifuge and dry to obtain modified graphite phase carbon nitride.
[0047] Example 5
[0048] Preparation of modified graphite phase carbon nitride:
[0049] S1. 100 g of melamine (AR; purchased from Tianjin Guangfu Technology Development Co., Ltd.) was placed in a covered ceramic crucible, and then placed in a muffle furnace (KSL-1200X; produced by Hefei Kejing Material Technology Co., Ltd.), and the temperature was increased to 560° C. at a heating rate of 10° C. / min, and the mixture was calcined at a constant temperature for 4 h. After the calcination was completed, the mixture was naturally cooled to room temperature to obtain a solid product, and the solid product was ground through a 400-mesh sieve to obtain bulk carbon nitride;
[0050] S2. Add 20 g of bulk carbon nitride to 200 mL of 95% sulfuric acid (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) with stirring, stir magnetically for 2 h, filter, and collect solid components, wherein the bulk carbon nitride is treated with acid to reduce the interlayer bonding force and achieve peeling, and the obtained solid component is mainly graphite phase carbon nitride. Wash the solid component with deionized water until it is neutral, and then place the washed solid component in 200 mL of 50% ethanol-pure water solution (prepared with anhydrous ethanol; anhydrous ethanol is purchased from Sinopharm Chemical Reagent Co., Ltd.) with a volume fraction of 50%, ultrasonically stir for 50 min, and then add 30 g of the fluorine-containing silane compound prepared in Example 2 above with stirring, continue ultrasonic stirring for 5 h, and after the ultrasonic stirring is completed, centrifuge and dry to obtain modified graphite phase carbon nitride.
[0051] Example 6
[0052] Preparation of modified graphite phase carbon nitride:
[0053] S1. 100 g of guanidine hydrochloride (AR; purchased from Tianjin Guangfu Technology Development Co., Ltd.) was placed in a covered ceramic crucible, and then placed in a muffle furnace (KSL-1200X; produced by Hefei Kejing Material Technology Co., Ltd.), and the temperature was increased to 580° C. at a heating rate of 11° C. / min, and the constant temperature was continuously calcined for 4 h. After the calcination was completed, the mixture was naturally cooled to room temperature to obtain a solid product, and the solid product was ground through a 400-mesh sieve to obtain bulk carbon nitride;
[0054] S2. Add 20 g of bulk carbon nitride to 200 mL of 95% sulfuric acid (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) with stirring, stir for 2 h, filter, and collect solid components, wherein the bulk carbon nitride is treated with acid to reduce the interlayer bonding force and achieve peeling, and the obtained solid component is mainly graphite phase carbon nitride. Wash the solid component with deionized water until it is neutral, and then place the washed solid component in 200 mL of 50% ethanol-pure water solution (prepared with anhydrous ethanol; anhydrous ethanol is purchased from Sinopharm Chemical Reagent Co., Ltd.) with ultrasonic stirring for 50 min, and then add 30 g of the fluorine-containing silane compound prepared in Example 3 above with stirring, continue ultrasonic stirring for 5 h, and after the ultrasonic stirring is completed, centrifuge and dry to obtain modified graphite phase carbon nitride.
[0055] Comparative Example 1
[0056] Comparative Example 1 is the control group of Example 5, where 30 g of the fluorine-containing silane compound prepared in Example 2 in S1 of Example 5 is replaced with 30 g of (3-epoxypropoxy)propyltrimethoxysilane (98%; purchased from Sinopharm Chemical Reagent Co., Ltd.), and the remaining raw materials, raw material amounts and preparation methods remain unchanged, and modified graphite phase carbon nitride is finally obtained.
[0057] Comparative Example 2
[0058] Comparative Example 2 is a control group of Example 5, in which 30 g of the fluorine-containing silane compound prepared in Example 2 above in S1 of Example 5 is removed, and the remaining raw materials, raw material amounts and preparation methods remain unchanged, and finally graphite phase carbon nitride is obtained. Specifically, the preparation process of graphite phase carbon nitride is as follows:
[0059] Preparation of graphite phase carbon nitride:
[0060] S1. 100 g of melamine (AR; purchased from Tianjin Guangfu Technology Development Co., Ltd.) was placed in a covered ceramic crucible, and then placed in a muffle furnace (KSL-1200X; produced by Hefei Kejing Material Technology Co., Ltd.), and the temperature was increased to 560° C. at a heating rate of 10° C. / min, and the mixture was calcined at a constant temperature for 4 h. After the calcination was completed, the mixture was naturally cooled to room temperature to obtain a solid product, and the solid product was ground through a 400-mesh sieve to obtain bulk carbon nitride;
[0061] S2. Add 20 g of bulk carbon nitride to 200 mL of 95% sulfuric acid (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) with stirring, magnetically stir for 2 hours, filter, and collect solid components, wherein the bulk carbon nitride is treated with acid to reduce the interlayer bonding force and achieve peeling, and the obtained solid component is mainly graphite phase carbon nitride. The solid component is then washed with deionized water until it is neutral, and the washed solid component is placed in 200 mL of 50% ethanol-pure water solution (prepared with anhydrous ethanol; anhydrous ethanol was purchased from Sinopharm Chemical Reagent Co., Ltd.) with a volume fraction of 50%, ultrasonically stirred for 50 minutes, and then ultrasonically stirred for 5 hours. After the ultrasonic stirring is completed, it is centrifuged and dried to obtain graphite phase carbon nitride.
[0062] Example 7
[0063] Preparation of acid and alkali resistant and corrosion resistant silicone tube:
[0064] First, the acid-resistant, alkali-resistant and corrosion-resistant silicone tube includes the following raw materials by weight:
[0065] 100 parts of methyl vinyl silicone rubber;
[0066] 22 parts of modified graphite phase carbon nitride prepared in Example 4;
[0067] 13 parts of white carbon black;
[0068] 12 parts of polymethyl hydrogen siloxane;
[0069] 2 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;
[0070] 1 part of platinum catalyst;
[0071] Then, the preparation method of the acid-resistant, alkali-resistant and corrosion-resistant silicone tube comprises the following steps:
[0072] Mixing: according to the above weight parts, the raw materials methyl vinyl silicone rubber (SR-35; Henan Tuoren Medical Instrument Co., Ltd.), the modified graphite phase carbon nitride prepared in Example 4, white carbon black (purchased from Sinopharm Chemical Reagent Co., Ltd.), polymethyl hydrogen siloxane (Mn=1700-3200; purchased from Sinopharm Chemical Reagent Co., Ltd.), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (purchased from Sinopharm Chemical Reagent Co., Ltd.) and platinum catalyst (AR; purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.) are weighed, and then the methyl vinyl silicone rubber, the modified graphite phase carbon nitride prepared in Example 4, white carbon black, activator, polymethyl hydrogen siloxane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and platinum catalyst are mixed and placed in an internal mixer for mixing. The speed of the internal mixer is 30r / min, and the mixing time is 20min. After mixing, a silica gel material is obtained;
[0073] Extrusion: The silicone material is placed in a silicone extruder for extrusion molding. The extrusion temperature of the silicone extruder is 145°C and the extrusion rate is 5m / min. After extrusion, a silicone tube is obtained;
[0074] Vulcanization: Place the silicone tube in a vulcanization furnace for vulcanization treatment. The vulcanization pressure is 8MPa. The vulcanization treatment includes primary vulcanization and secondary vulcanization. The temperature of the primary vulcanization is 165℃ and the time of the primary vulcanization is 20min. After the primary vulcanization is completed, secondary vulcanization is carried out. The temperature of the secondary vulcanization is 210℃ and the time of the secondary vulcanization is 1.5h. After the vulcanization treatment is completed, it is cooled to room temperature, and then inspected and packaged to obtain an acid, alkali and corrosion-resistant silicone tube.
[0075] Example 8
[0076] Preparation of acid and alkali resistant and corrosion resistant silicone tube:
[0077] First, the acid-resistant, alkali-resistant and corrosion-resistant silicone tube includes the following raw materials by weight:
[0078] 100 parts of methyl vinyl silicone rubber;
[0079] 25 parts of modified graphite phase carbon nitride prepared in Example 5;
[0080] 14 parts of white carbon black;
[0081] 14 parts of polymethyl hydrogen siloxane;
[0082] 2 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;
[0083] 2 parts of platinum catalyst;
[0084] Then, the preparation method of the acid-resistant, alkali-resistant and corrosion-resistant silicone tube comprises the following steps:
[0085] Mixing: according to the above weight parts, the raw materials methyl vinyl silicone rubber (SR-35; Henan Tuoren Medical Instrument Co., Ltd.), the modified graphite phase carbon nitride prepared in Example 5, white carbon black (purchased from Sinopharm Chemical Reagent Co., Ltd.), polymethyl hydrogen siloxane (Mn=1700-3200; purchased from Sinopharm Chemical Reagent Co., Ltd.), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (purchased from Sinopharm Chemical Reagent Co., Ltd.) and platinum catalyst (AR; purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.) are weighed, and then the methyl vinyl silicone rubber, the modified graphite phase carbon nitride prepared in Example 5, white carbon black, activator, polymethyl hydrogen siloxane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and platinum catalyst are mixed and placed in an internal mixer for mixing. The speed of the internal mixer is 40r / min, and the mixing time is 30min. After mixing, a silica gel material is obtained;
[0086] Extrusion: The silicone material is placed in a silicone extruder for extrusion molding. The extrusion temperature of the silicone extruder is 155°C and the extrusion rate is 10m / min. After extrusion, a silicone tube is obtained;
[0087] Vulcanization: Place the silicone tube in a vulcanization furnace for vulcanization treatment. The vulcanization pressure is 10MPa. The vulcanization treatment includes primary vulcanization and secondary vulcanization. The temperature of the primary vulcanization is 170℃ and the time of the primary vulcanization is 30min. After the primary vulcanization is completed, secondary vulcanization is carried out. The temperature of the secondary vulcanization is 220℃ and the time of the secondary vulcanization is 2h. After the vulcanization treatment is completed, it is cooled to room temperature, and then inspected and packaged to obtain acid, alkali and corrosion-resistant silicone tube.
[0088] Example 9
[0089] Preparation of acid and alkali resistant and corrosion resistant silicone tube:
[0090] First, the acid-resistant, alkali-resistant and corrosion-resistant silicone tube includes the following raw materials by weight:
[0091] 100 parts of methyl vinyl silicone rubber;
[0092] 25 parts of modified graphite phase carbon nitride prepared in Example 6;
[0093] 15 parts of white carbon black;
[0094] 15 parts of polymethyl hydrogen siloxane;
[0095] 3 parts of 2,4-dichlorobenzoyl peroxide;
[0096] 3 parts of platinum catalyst;
[0097] Then, the preparation method of the acid-resistant, alkali-resistant and corrosion-resistant silicone tube comprises the following steps:
[0098] Mixing: according to the above weight parts, the raw materials methyl vinyl silicone rubber (SR-35; Henan Tuoren Medical Instrument Co., Ltd.), the modified graphite phase carbon nitride prepared in Example 6, white carbon black (purchased from Sinopharm Chemical Reagent Co., Ltd.), polymethyl hydrogen siloxane (Mn=1700-3200; purchased from Sinopharm Chemical Reagent Co., Ltd.), 2,4-dichlorobenzoyl peroxide (98%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and platinum catalyst (AR; purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.) are weighed, and then the methyl vinyl silicone rubber, the modified graphite phase carbon nitride prepared in Example 6, white carbon black, activator, polymethyl hydrogen siloxane, 2,4-dichlorobenzoyl peroxide and platinum catalyst are mixed and placed in an internal mixer for mixing. The speed of the internal mixer is 50r / min, and the mixing time is 30min. After mixing, a silica gel material is obtained;
[0099] Extrusion: The silicone material is placed in a silicone extruder for extrusion molding. The extrusion temperature of the silicone extruder is 160°C and the extrusion rate is 15m / min. After extrusion, a silicone tube is obtained;
[0100] Vulcanization: Place the silicone tube in a vulcanization furnace for vulcanization treatment. The vulcanization pressure is 10MPa. The vulcanization treatment includes primary vulcanization and secondary vulcanization. The temperature of the primary vulcanization is 175℃ and the time of the primary vulcanization is 30min. After the primary vulcanization is completed, secondary vulcanization is carried out. The temperature of the secondary vulcanization is 220℃ and the time of the secondary vulcanization is 2h. After the vulcanization treatment is completed, it is cooled to room temperature and then inspected and packaged to obtain an acid, alkali and corrosion-resistant silicone tube.
[0101] Comparative Example 3
[0102] Comparative Example 3 is the control group of Example 8, in which the modified graphite phase carbon nitride prepared in Example 5 in Example 8 is replaced by the modified graphite phase carbon nitride prepared in Comparative Example 1, and the other raw materials, raw material amounts and preparation methods remain unchanged, and finally an acid-, alkali- and corrosion-resistant silicone tube is obtained.
[0103] Comparative Example 4
[0104] Comparative Example 4 is the control group of Example 8, in which the modified graphite phase carbon nitride prepared in Example 5 in Example 8 is replaced by the graphite phase carbon nitride prepared in Comparative Example 2, and the other raw materials, raw material amounts and preparation methods remain unchanged, and finally an acid-, alkali- and corrosion-resistant silicone tube is obtained.
[0105] Comparative Example 5
[0106] Comparative Example 5 is the control group of Example 8, in which the modified graphite phase carbon nitride prepared in Example 5 in Example 8 is removed, and the remaining raw materials, raw material amounts and preparation methods remain unchanged, and finally an acid-, alkali- and corrosion-resistant silicone tube is obtained.
[0107] Test Example 1
[0108] The present invention refers to the method disclosed in the prior art, adopts gas chromatography and mass spectrometry, and uses an acidic solution (sodium formate buffer with pH = 3.25; purchased from Shanghai Yuanye Biotechnology Co., Ltd.; No. R26362) and an alkaline solution (PBS phosphate buffer with pH = 10.5; purchased from Shanghai Yuanye Biotechnology Co., Ltd.; No. R27204) commonly transported by silicone tubes in medicine as corrosive solvents to respectively corrode the acid-base corrosion-resistant silicone tubes (hereinafter referred to as: silicone tubes) prepared in Examples 7 to 9 and Comparative Examples 3 to 5, and the contents of the four cyclosiloxanes in the acid / alkaline corrosion solutions after corrosion are determined. The determination results are shown in Table 1 below, and the test-related conditions / parameters are disclosed as follows:
[0109] a. Standard reagents: hexamethylcyclotrisiloxane (D3; 97%; purchased from Sinopharm Chemical Reagent Co., Ltd.), octamethylcyclotetrasiloxane (D4; 96%; purchased from Sinopharm Chemical Reagent Co., Ltd.), decamethylcyclopentasiloxane (D5; 99%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and dodecamethylcyclohexasiloxane (D6; 97%; purchased from Sinopharm Chemical Reagent Co., Ltd.).
[0110] b. Acid / alkaline corrosion / blank solution: Take 50 mL of sodium formate buffer with a pH value of 3.25 and place it in a silicone tube, then place it in an oven at 40°C for 24 hours, take it out and cool it to room temperature, collect the sodium formate buffer to obtain an acidic corrosion solution; then take 50 mL of PBS phosphate buffer with a pH value of 10.5 and place it in a silicone tube, then place it in an oven at 40°C for 24 hours, take it out and cool it to room temperature, collect the PBS phosphate buffer to obtain an alkaline corrosion solution.
[0111] c. Experimental conditions: The chromatographic column is an HP-5MS column (30.0m length × 0.25mm inner diameter × 0.25μm film thickness); the injection port temperature is 220℃; the auxiliary heater temperature is 150℃; the initial column temperature is 40℃, maintained for 1min, then increased to 220℃ at a rate of 10℃ / min, and then increased to 300℃ at a rate of 50℃ / min, maintained for 2min; the carrier gas is helium, and the carrier gas flow rate is 1.0mL / min; the injection method is splitless injection, and the injection volume is 1μL.
[0112] Referring to the above test conditions / parameters, the contents of D3, D4, D5 and D6 in the acidic corrosion solution / alkaline corrosion solution were determined by gas chromatography-mass spectrometer (model GC-MS2010; purchased from Shimadzu Corporation) in ng / mL, and recorded in Table 1 below.
[0113]
[0114] It can be seen from Table 1 that in the process of transporting acid / alkaline liquid, compared with Comparative Examples 3 to 5, the silicone rubber prepared in Examples 7 to 9 of the present invention has significantly reduced content of cyclosiloxane migrating into the liquid, and the contamination of the liquid is significantly reduced. Therefore, the silicone tubes prepared in Examples 7 to 9 of the present invention have excellent acid and alkali corrosion resistance.
[0115] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.
[0116] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An acid-resistant, alkali-resistant and corrosion-resistant silicone tube, characterized in that: Including the following raw materials by weight: 100 parts of methyl vinyl silicone rubber; 22-25 parts of modified graphite phase carbon nitride; 13-15 parts of white carbon black; 12-15 parts of polymethyl hydrogen siloxane; 2-3 parts of vulcanizing agent; 1 to 3 parts of platinum catalyst; The modified graphite phase carbon nitride is prepared by the following steps: S1. Place a nitrogen-containing compound in a crucible, then place it in a muffle furnace, heat it to 550-580°C at a heating rate of 9-11°C / min, and continue calcining at a constant temperature for 3-4 hours. After calcination, cool it naturally to room temperature to obtain a solid product, grind the solid product through a 400-mesh sieve to obtain bulk carbon nitride; S2. Stirring bulk carbon nitride into 95% sulfuric acid, stirring magnetically for 1-2 hours, filtering, collecting solid components, washing the solid components with deionized water until neutral, placing the washed solid components in a 50% volume fraction ethanol-pure water solution, stirring ultrasonically for 30-50 minutes, stirring and adding the fluorine-containing silane compound, continuing ultrasonic stirring for 4-5 hours, and after the ultrasonic stirring is completed, centrifuging and drying to obtain modified graphite phase carbon nitride; The fluorine-containing silane compound is prepared by the following steps: N,N-dimethylformamide is added to the reactor with stirring, and nitrogen is filled in for protection. Tridecafluorooctanol and (3-epoxypropoxy)propyltrimethoxysilane are added thereto with stirring, and the mixture is mixed for 3 to 5 minutes. The mixture is heated to 40 to 50° C. and stirred at a constant temperature for 5 to 10 minutes. Triethylamine is added thereto with stirring. After the addition of triethylamine is completed, the mixture is heated to 140 to 155° C. and stirred at a constant temperature for 5 to 6 hours. After the stirring is completed, the mixture is cooled to room temperature to obtain a mixture. After the mixture is subjected to reduced pressure distillation, Amberlyst-15 ion exchange resin is added thereto with stirring, and the mixture is stirred at room temperature for 20 to 30 minutes to adsorb the remaining catalyst triethylamine. After the stirring is completed, the mixture is filtered and the filtrate is collected to obtain a fluorine-containing silane compound.
2. The acid-resistant, alkali-resistant and corrosion-resistant silicone tube according to claim 1, characterized in that: The nitrogen-containing compound is one of urea, melamine and guanidine hydrochloride.
3. The acid-resistant, alkali-resistant and corrosion-resistant silicone tube according to claim 1, characterized in that: The usage ratio of 95% sulfuric acid, bulk carbon nitride, 50% ethanol-pure water solution, and fluorine-containing silane compound in S2 is 200mL:20g:200mL:25-30g.
4. The acid-resistant, alkali-resistant and corrosion-resistant silicone tube according to claim 1, characterized in that: The dosage ratio of the N,N-dimethylformamide, tridecafluorooctanol, (3-epoxypropoxy)propyltrimethoxysilane, triethylamine and Amberlyst-15 ion exchange resin is 500 mL: 0.1-0.11 mol: 0.1-0.105 mol: 8.5-10.5 g: 4.5-5.0 g.
5. The acid-resistant, alkali-resistant and corrosion-resistant silicone tube according to claim 1, characterized in that: The vulcanizing agent is one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 2,4-dichlorobenzoyl peroxide.
6. A method for preparing an acid-resistant, alkali-resistant, and corrosion-resistant silicone tube according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing: Weigh the raw materials according to their weight and mix them in an internal mixer for mixing. The speed of the internal mixer is 30-50 r / min and the mixing time is 20-30 min. After mixing, a silica gel material is obtained; Extrusion: The silicone material is placed in a silicone extruder for extrusion molding. The extrusion temperature of the silicone extruder is 145-160°C and the extrusion rate is 5-15m / min. After extrusion, a silicone tube is obtained; Vulcanization: Place the silicone tube in a vulcanization furnace for vulcanization treatment. After the vulcanization treatment is completed, cool it to room temperature, and then inspect and package it to obtain an acid-resistant, alkali-resistant, and corrosion-resistant silicone tube.
7. The method for preparing an acid-resistant, alkali-resistant and corrosion-resistant silicone tube according to claim 6, characterized in that: The vulcanization treatment includes primary vulcanization and secondary vulcanization.
8. The method for preparing an acid-resistant, alkali-resistant and corrosion-resistant silicone tube according to claim 7, characterized in that: The temperature of the primary vulcanization is 165-175° C., and the time of the primary vulcanization is 20-30 minutes. After the primary vulcanization is completed, the secondary vulcanization is carried out, and the temperature of the secondary vulcanization is 210-220° C., and the time of the secondary vulcanization is 1.5-2 hours.